Extracorporeal membrane oxygenation in children with heart disease and del22q11 syndrome: a review of the Extracorporeal Life Support Organization Registry. (November 2015) - Prodhan, P; Gossett, JM; Rycus, PT; Gupta, P
The study objective was to evaluate outcomes among children with del22q11 (DiGeorge) syndrome supported on ECMO for heart disease. The ELSO registry database was queried to include all children <18 years undergoing heart surgery for either common atrio-ventricular canal, tetralogy of Fallot, truncus arteriosus or transposition of the great vessels and interrupted aortic arch and requiring ECMO, from 1998-2011. The outcomes evaluated included mortality, ECMO duration and length of hospital stay in patients with del22q11 syndrome and with no del22q11 syndrome. Eighty-eight ECMO runs occurred in children with del22q11 syndrome while 2694 ECMO runs occurred in children without del22q11 syndrome. For patients with heart defects receiving ECMO, del22q11 syndrome did not confer a significant mortality risk or an increased risk of infectious complications before or while on ECMO support. Neither the duration of ECMO nor mechanical ventilation prior to ECMO deployment were prolonged in patients with del22q11 syndrome compared to the controls.